Analisis Faktor Eksternal terhadap Perilaku Belajar Siswa SMA Patra Dharma Kota Balikpapan - Tutik Yuliani (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2019)
This study aims to determine the effect of family environment and peer interaction on the learning behavior of XI SMA Patra Dharma Balikpapan students. Samples were obtained by means of random or random sampling techniques, with a sample of 95 students. How to collect data in this study by distributing questionnaires to class XI students of Patra Dharma High School students. To prove the hypothesis in this study by using t test and F test. The results of this study indicate that partially family environment, peer interaction affects the learning behavior of class XI students of Patra Dharma High School Balikpapan, this is shown by looking at the value of t count 2.223> t table 1,660 for family environment variables and t count 2,946> t table 1,660 for peer interaction. Whereas simultaneously the family environment, peer interaction affects the learning behavior of XI Patra Dharma Balikpapan class XI students, this is indicated by the calculated F value of 9.204 greater than Ftable = 3,098.